Advancing Sustainable Entrepreneurship Technology through Campus Environmental Education, Green Accounting, and Sustainability Competencies - Julita Julita; Edfan Darlis; Bunga Chintia Utami; Diah Anugrah Dipuja; Kiswanto Kiswanto; M. Yogi Riyantama Isjoni; Frini Karina Andini; Riska Natariasari; Ria Nelly Sari; Susi Hendriani; Muhammad Luthfi Iznillah; Machasin Machasin (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: This research aims to investigate the influence of Sustainability Education, Campus Sustainability, and Environmental Sustainability on Entrepreneurship for Sustainability among university students. It also examines the moderating roles of Sustainability Competencies and Awareness of Green Accounting in strengthening or weakening these relationships, providing a more comprehensive understanding of the factors that promote sustainable entrepreneurship in higher education. Method: A quantitative research design with a survey approach was employed. The participants consisted of 753 students from Universitas Riau, Indonesia, selected using a convenience sampling technique. Primary data were collected through an online questionnaire, and the proposed model was analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 3.0 to evaluate both direct and moderating effects among the variables. Results: The findings show that Sustainability Education, Sustainability Competencies, and Awareness of Green Accounting positively and significantly influence Entrepreneurship for Sustainability. Sustainability Competencies and Awareness of Green Accounting also strengthen the effects of other variables, while Campus Sustainability and Environmental Sustainability do not have significant direct effects. Moderation analysis indicated positive interactions for Sustainability Education and negative interactions for Campus Sustainability and Environmental Sustainability. Novelty: The novelty lies in integrating Sustainability Competencies and Awareness of Green Accounting as both direct predictors and moderating variables in explaining Entrepreneurship for Sustainability. This model offers a more comprehensive framework for promoting sustainable entrepreneurship in higher education.